CAPITAL STRUCTURE AND SHAREHOLDER WEALTH MAXIMIZATION IN INDIAN AUTOMOBILE COMPANIES: AN EMPIRICAL ANALYSIS - Kansal, Ayush; Sharma, Swati Oza (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The automobile industry in India is one of the most capital-intensive sectors, making financing decisions crucial for sustaining growth and competitiveness. This study investigates the impact of capital structure on shareholder wealth maximization in Indian automobile companies over a ten-year period (2012–2022). Using data from 30 listed firms, the research applies descriptive statistics, correlation, multiple regression, ANOVA, and Structural Equation Modeling (SEM) to examine the relationships between debt-equity ratios, cost of borrowing, profitability measures (ROA, ROE, EPS), dividend policy, and shareholder wealth indicators (market price, EPS, dividend per share). The results demonstrate that capital structure significantly affects shareholder wealth both directly and indirectly through profitability. Excessive leverage negatively impacts returns and market valuation, while moderate debt enhances value by balancing tax benefits and financial risk, consistent with trade-off theory. The study also finds that profitability is the strongest mediator linking financing choices to investor wealth, cost of borrowing exerts a detrimental effect, and dividend policy serves as a positive signal of financial stability. The findings contribute to the literature on corporate finance in emerging markets by providing sector-specific evidence from India’s automobile industry. Managerial and policy implications suggest that firms should maintain an optimal debt-equity mix, manage borrowing costs efficiently, and adopt stable dividend policies to maximize long-term shareholder wealth.